Perftoran improves Visudyne-photodynamic therapy via suppressing hypoxia pathway in murine lung cancer. Issue 1 (March 2022) - Gamal-Eldeen, Amira M.; Alrehaili, Amani A.; Alharthi, Afaf; Banjer, Hamsa J.; Raafat, Bassem M.; Hawsawi, Nahed M.
Abstract: Perfluorodecalin emulsion (Perftoran®) is an oxygen carrier. Verteporfin, a photosensitizer, is used for cancer photodynamic therapy (PDT) in its liposomal form (Visudyne®). Hypoxia affects PDT efficacy. The study aimed to investigate the effect of Perftoran® on the efficacy of Visudyne®/PDT and on the hypoxia pathway in lung cancer. Lung cancer was induced in mice by diethylnitrosamine and carbon tetrachloride. Lung tissues have been analyzed for apoptosis and necrosis detection by dual DNA staining; mitochondrial transmembrane potential (ΔΨm) staining by Red CMX-Ros, hypoxia estimation by pimonidazole, miRNA-21-5p and miRNA-210-3p evaluation by qPCR, and HIF-1α and VEGF determination by ELISA. Compared to Visudyne®/PDT, Perftoran®/Visudyne®/PDT led to severe apoptosis and necrosis regions in the bronchiolar epithelium, induced late apoptosis and necrosis and suppressed ΔΨm and total hypoxia level more than Visudyne®/PDT. The expression of miR-21 and miR-210 and the concentration of HIF-1α and VEGF were significantly induced in tumor-bearing mice. Compared to Visudyne®/PDT, Perftoran®/Visudyne®/PDT dramatically suppressed the expression of miR-21 and miR-210 and the concentration of HIF-1α and VEGF. In conclusion, these findings indicate the potential role of Perftoran® in suppressing hypoxia through the inhibition of the hypoxamiRs expression and HIF-1α, which in turn led to the inhibition of VEGF, during Visudyne®/PDT.